Supraclavicular Artery Island Flap in Head-and-neck Reconstruction: Our Experience - Abhinav Thaduri; Bhinyaram Jat; Amit Kumar; Amit Kumar Tyagi; Abhijeet Singh; Vikramjit Singh Kailey; Dileep Dungala Maharaj; Shahab Usmani; Kartikesh Gupta (Journal of Head & Neck Physicians and Surgeons)
Background: Reconstruction of head-and-neck cancer defects is a challenging task, keeping in mind the complexity of the defects. Locoregional pedicle flap reconstruction is not an inferior option. The supraclavicular flap gained popularity in 1997 to reconstruct mentosternal contractures in postburn patients. This is a perforator-based pedicled, axial, and fasciocutaneous flap based on the supraclavicular artery. This study aims to examine a series of cases with pedicled supraclavicular flap reconstruction in head-and-neck cancers. Methods: This study is a retrospective review of patient data from our institution from 2018 to 2020. A total of seven patients were included who underwent surgical resection for various head-and-neck cancers. Surgical defects were reconstructed with a supraclavicular islanded fasciocutaneous flap. Results: All patients underwent wide excision of the tumor following oncological principles, and four out of seven patients received postoperative adjuvant radiotherapy. Two patients with parotid tumors underwent facial skin excision along with total parotidectomy. Both cases were recurrent. One patient had partial necrosis of the distal part of the flap. Two patients required split-thickness skin graft for the closure of the donor site. Conclusion: Supraclavicular artery island flap (SCAIF) is one of the good reconstructive options for midline neck defects, simple oral cavity defects, and cheek skin defects. It is an excellent alternative to free tissue transfer with limited donor-site morbidity. Careful selection of patients is key to successful reconstruction using a SCAIF in the head-and-neck region.